Kinetic Study of Decolorization of Methylene Blue with Sodium Sulphite in Aqueous Media: Influence of Transition Metal Ions - Olajire, A. A.; Olajide, A. J. (My University, 2014)
The kinetics of decolorization of methylene blue (MB+) with sodium sulphite in aqueous media was investigated over the temperature range 20-40°C. The kinetic studies were carried out as a function of different variables like concentration, pH, and temperature on rate of decolorization. The rate of the reaction was found to be [H+] dependent and first order in both [MB+] and reductant. The empirical rate law conforms to the equation: Where K1 is the protonation constant, and k2 and k3 are overall pseudo-second order rate constants for the decolorization of MB+ with 2 3 SO − . The rate was found to increase linearly with temperature. The rate of decolorization decreased after addition of Co(II), Ni(II), Mn(II) and Zn(II), but increased after addition of Fe(II) and Cu(II). The activation parameters (Ea, ΔG#, ΔH# and ΔS#) of the decolorization reaction of MB+ with 2 3 SO − in absence and in presence of Fe(II) and Cu(II) were calculated.
Keywords: Methylene blue; Sodium sulphite; Metal activation; Kinetics; Decolorization